(untitled) (Bangladesh Journal of Botany, 2019)
The utilization patern of plant resources of Pin Punjal Mountanious range of Azad Kashmir and anthropogenic stress of the ecosystem was documented. A total of 150 species were recorded by the local people for various needs, such as, 19 species used as fruit and vegetables, 47 as medicinal, 26 as fuel wood, 12 as timber for furniture making, 32 as fodder for grazing of livestock, 4 as ornamental and 10 as aesthetic for cultural and religious activities. The anthropogenic pressure on the ecosystem was analysed by using principal components analysis (PCA) which resulted significant anthropogenic stressors on the natural resources of the area.